THE VOICE OF EXPERIENCE: PORTRAITS AND CHALLENGES IN TEACHING BIOLOGY IN CONTEMPORARY TIMES - Moura, Maria Caroline Rodrigues; dos Santos Fontes, André; de Sousa Rocha, Bruna Cardoso; de Moura Vale, Ceres; Almeida, Maria Karoline Carvalho; de Sá Ribeiro, Ludmylla; das Neves Silva, Luiz Eduardo; da Cunha Gonzaga Silva, Patricia (Seven Editora, 2025)
This study seeks to analyze the portraits and challenges of contemporary biology teaching through the accounts of teachers from the municipality of Picos, Piauí, and neighboring regions. Teachers' experiences with biology teaching present many challenges, especially motivating students to learn scientific and biological knowledge. This study, through qualitative research using questionnaires, interviewed teachers, and the data were analyzed using content analysis. This study hopes to contribute to a better understanding of teachers' motivations, challenges, and classroom experiences in basic education biology, with an emphasis on practices, training, and expectations in the profession.DOI: https://doi.org/10.56238/sevened2025.030-061